Diagnostic laparoscopy in chronic abdominal diseases - Mishra, Navneet; Sharma, Shrikant (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Objectives: To establish an early diagnosis of the diseases where clinical findings are unreliable, with additional information about extent, nature, morbid changes and operability of the diseases andto establish that laparoscopy can prevent diagnostic laparotomy. Methodology: The present study was carried out in 32 patients admitted in surgical, medical, gynaecological and cancer wards.The patients were followed and planned for further management according to the laparoscopic findings either conservatively or exploratory. The patients having inoperable malignancy were referred to cancer hospital for further medical management and patients with koch’s abdomen were started antitubercular treatment. Results: Laproscopy was helpful in confirming the clinical diagnosis in 46.875% of cases, itsolved the diagnostic dilemma in 34.375% of cases and in 9.375% the clinical impression was foundwrong which was corrected by laparoscopy. In 9.375% of cases diagnostic laparoscopy was done with the intention of looking secondary deposits, if present, to stage the malignancy. As compared to clinical diagnosis laparoscopic diagnosis was proved wrong in 3.125% cases, later on during laprotomy. Conclusion: Laparoscopy is a safe, simple, accurate and useful diagnostic modality in the general surgical practice. It is cost effective and can be used in critically ill patients. Thus laparoscopy has a significant diagnostic and therapeutic role in patients with chronic abdominal pain.